Che cosa è l'umano? A proposito del postumano: confronto con Rosi Braidotti - Bello, Angela Ales (B@belonline, 2024)
In my paper I examine Braidotti’s books: The Posthuman (2013), Posthuman Knowledge (2019), Posthuman Feminism (2021). In order to show her point of view, I pinpoint the outlines of this new philosophical approach, and I compare some of them with a phenomenological approach and even with some proposal that we find in Pope Francis’ doctrinal writings. I appreciate very much Rosi Braidotti’s critical attitude and the novelty of her position, at the same time I think that some of her theoretical statements appear to be problematic, for this reason they need to be discussed and clarified.